If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4t + -13 = 19 Reorder the terms: -13 + 4t = 19 Solving -13 + 4t = 19 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '13' to each side of the equation. -13 + 13 + 4t = 19 + 13 Combine like terms: -13 + 13 = 0 0 + 4t = 19 + 13 4t = 19 + 13 Combine like terms: 19 + 13 = 32 4t = 32 Divide each side by '4'. t = 8 Simplifying t = 8
| 7(x-1)=5-2x | | 12x+6=10x+16 | | 15a+1=46 | | 6+x=2(x+6)+6 | | 7(x-2)=5-2x | | 5q-4=6 | | 4a+2=4a+7 | | 3e=6 | | 13x-274=4x-13 | | 2x^2+17x+34=0 | | 2x^2-4=14 | | 32x=-15y | | 3x-2=24 | | 3x^2+16x+34=0 | | 32x+15y=0 | | 6x+7=2x-19 | | (x-3)(x+6)=x-7 | | 987+456= | | 5(x-5)=8(x+3) | | 5.7m-13.75=8.2n | | (x+4)=4 | | 11q=12 | | 6g=12 | | 2x-4=-10 | | x=2(4)+2(4) | | 6(10+x)=120 | | x-(-9)=57 | | 5x-3y=-3 | | 4(x+7)=4x+1 | | 4x-3=x+12 | | 1+11x=121+x | | 5.6x-1=-1+6x |